Probing the binding hypothesis of Smad3 modulators by molecular dynamic simulations for Atherosclerosis Cardiovascular Disease (ASCVD) - Ubair Aziz; Ishrat Jabeen (PLoS ONE, 2025)
Transforming Growth Factor β (TGFβ) pathway has been recognized as one of the major processes involved in fibrotic diseases including the Atherosclerosis Cardiovascular Disease (ASCVD). Many drugs have been proposed and are under clinical trials for modulation of the TGFβ pathway by targeting TGFβ receptor. Recently, various proof of the concept studies have advocated that the inhibition of TGFβ-mediated Smad pathway could produce more focused effect with less off target toxicities in ASCVD. As these studies lack the mechanism and binding profile of Smad3 modulators, characterization of binding pattern for Smad3 inhibitors can provide a platform for the lead optimization against ASCVD. We utilized dimeric inhibitors from the PubChem dataset (PubChem ID: 630) of Smad3-FoxH1 binding inhibitors to generate binding hypothesis of Smad3 inhibitors. The selected compounds from the dataset were docked and ligand-protein complexes were simulated for 250 ns for further sampling of conformational space and to obtain stable binding hypothesis. Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF) and hydrogen bond analysis of ligand-protein complexes after simulations revealed that Asn320 in Smad3 provides an efficient inhibition site for the two most potent small inhibitors (hereby named SM1 and SM2) of Smad3-FoxH1 binding. Although the diverse nature of compounds produce variable interaction patterns with FoxH1 binding site in Smad3, Gln315, Gln364 and Arg367 were observed to be the most common hydrogen bond interaction points in this binding site. Additionally, two compounds (hereby named SM8 and SM19) detached from the FoxH1 binding site and formed a highly stable complex around Tyr323 via hydrophobic complementarity, suggesting a new binding site for modulation of Smad3 activity.